Water and nitrogen needs of wheat (Triticum aestivum) in sodic soil - Kumar, Ashok; Sharma, D K; Sharma, H C (The Indian Journal of Agricultural Sciences, 2012)
A field experiment was conducted during the winter season of 1990-91 and 1991Â·-92 to evaluate the effect of irrigation and nitrogen on wheat (Triticum aestivum L. emend. Fiori & Paol.) grown on sodic soil. Frequent irrigation at 1.2 irrigation water depth; cumulative pan evaporation (IW : CPE) ratio (IW â‰ˆ 50 mm) with 180 kg N/ha gave the highest grain yield of wheat (4 091 kg/ha). The rate of water use per day increased with advance in age, reaching the peak value of 3.58 mm/day during 60-90 days and was higher in irrigated crop (4.97 mm/day) under 1.2IW : CPE ratio than in the unirrigated (1.89 mm/day). More moisture was extracted from deeper layer (60-120 cm) under unirrigated condition than under irrigated condition. N application increased the moisture depletion from 0-60 cm Soil depth. The nitrate-nitrogen content of the soil was more under unirrigated condition than under irrigated one .It decreased with increase in irrigation frequency, but increased with higher level of N. At harvest it was higher in 15-30 cm than in 0-15 cm soil layer under 0.9 and 1.2 IW : CPE ratiosÂ